Comparative evaluation of microRNA-155 expression level and its correlation with tumor necrotizing factor α and interleukin 6 in patients with chronic periodontitis - Ahmad Mogharehabed; Jaber Yaghini; Ania Aminzadeh; Mahdi Rahaiee (Wolters Kluwer Medknow Publications, 2022)
Background: MicroRNAs are a class of small noncoding ribonucleic acids that perform a critical role in adjustment of gene expression. miRNAs-155 (miR-155) participates in controlling inflammation. Periodontitis is defined as inflammatory disorder of tissues surrounding the teeth. In this study, the expression levels of miR-155 and its target genes, tumor necrotizing factor alpha (TNF-α), and interleukin-6 (IL-6) were evaluated in a group of Iranian patients. Materials and Methods: This sectional study was performed on 10 healthy controls and 10 individuals with chronic periodontitis by means of polymerase chain reaction (PCR) test. For each individual, clinical parameters including probing depth and clinical attachment loss and blood samples were measured. Levels of miR-155, TNF-α, and IL-6 were quantified using real-time PCR (α=0/05) and the results were analyzed by Mann-Whitney U test. Results: The level of miR-155 was significantly higher in patients with chronic periodontitis (P < 0.001). A positive correlation was observed between the level of miR-155 and clinical parameters (P < 0.05). Level of miR-155 in tissue samples was correlated with blood samples although the expression level was higher in blood samples. Conclusion: As the expression level of miR-155, TNF-α, and IL-6 genes was higher in subjects with chronic periodontitis than healthy individuals, it might suggest a role for miR-155 in patients with chronic periodontitis.